Falling Weight Deflectometer Test Oriented Overlay Thickness Design: Case Study - Atiye Farahani; Hosein Zanjirani Farahani (Journal of Rehabilitation in Civil Engineering)
Falling Weight Deflectometer (FWD) can evaluate the assessment of structural conditions of pavements that require rehabilitation. Fifteen different pavement sections have been selected that six sections have located in Qom-Kashan Freeway, Iran and nine sections have located in Kashan-Qom Freeway, Iran to conduct FWD tests. FWD data have been analyzed to determine and monitor the structural adequacies of existing pavement sections includes the pavement deflection and load chart, the average deflection chart of seven geophones, and the calculated overlay thickness diagram for each station of each section. The results indicate that the average deflection for Direction: Qom-Kashan, is 6.7% less than Direction: Kashan-Qom. In this paper, the structural conditions of existing pavements have been assessed, and subsequently required overlay thickness values have been recommended from critical pavement responses computed from FWD field deflections. The results indicate that the surface of the pavement for Direction: Kashan-Qom needs 6.1% more overlay thickness than Direction: Qom-Kashan. Also, the Structural Condition Index (SCI) that is widely used on network and preliminary project level investigations has been calculated. Furthermore, a comparison is presented between calculated SCI before and after applying overlay and the effect of this index value on the pavement performance.